A rare appearance of a large mural thrombus in left atrium detected two years after the Maze procedure. Issue 2 (February 2016) - Taminishi, Shunta; Nomura, Tetsuya; Kubota, Hiroshi; Miyawaki, Daisuke; Urata, Ryota; Sugimoto, Takeshi; Higuchi, Yusuke; Kato, Taku; Keira, Natsuya; Doi, Kiyoshi; Yaku, Hitoshi; Tatsumi, Tetsuya
Abstract: A 77-year-old Japanese woman underwent bioprosthetic aortic valve replacement (AVR) and the Maze procedure for severe aortic valve disease and paroxysmal atrial fibrillation (AF), and one year after the AVR, she also underwent a permanent pacemaker implantation for sick sinus syndrome. At two postoperative years, a large mural mass happened to be detected in her left atrium on routine trans-thoracic echocardiography. The cardiac rhythm records produced by the implanted pacemaker demonstrated the recurrence of AF. As anticoagulant therapy was not effective at reducing the size of the mass, surgery was performed and organized thrombus was detected on the ablation line made at the Maze procedure. <Learning objective: The formation of large mural thrombi in the left atrium after the Maze procedure is rare in patients without mitral valve disease. The thrombus was considered to have been caused by several complex factors, including atrial wall damage brought by the Maze procedure and the recurrence of atrial fibrillation (AF). It is important to be aware that the recurrence of AF after the Maze procedure can carry a risk of unexpected mural thrombus formation in the left atrium.>